2006
DOI: 10.1002/aic.10820
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear observer of crystal‐size distribution during batch crystallization

Abstract: A high-gain observer was designed to estimate the crystal-size distribution (CSD) in batch crystallization processes. The observer is based on the discretization of population balance equations describing the evolution of the CSD using finite difference method. Due to process impurities and other batch-to-batch variations, the kinetic parameters involved in the dynamic model of the crystallization, relating primary and secondary nucleation in particular, are subject to significant variations. In order to avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…A great deal of effort for understanding the main factors that affect the MCS and the CSD has been reported in the literature. [1][2][3][4][5][6] Traditionally, mathematical modeling of particulate systems (e.g., crystallization) is based-on Structured Population Balances (SPB) [7][8][9][10] taking into account the effect of formation, growth, and coagulation of the CSD. However, detailed structured population models demand a comprehensive knowledge of the thermodynamic properties of all the components involved in the system under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of effort for understanding the main factors that affect the MCS and the CSD has been reported in the literature. [1][2][3][4][5][6] Traditionally, mathematical modeling of particulate systems (e.g., crystallization) is based-on Structured Population Balances (SPB) [7][8][9][10] taking into account the effect of formation, growth, and coagulation of the CSD. However, detailed structured population models demand a comprehensive knowledge of the thermodynamic properties of all the components involved in the system under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous-discrete systems are used in order to model processes having continuous state dynamics and a discrete measurement procedure, which reflects many practical situations. This approach is meaningful when the measurements sampling time is not constant, or when state estimates are needed between updates (Ahmed-Ali, Postoyan, & Lamnabhi-Lagarrigue, 2009;Astorga, Othman, Othman, Hammouri, & McKenna, 2002;Andrieu, Nadri, Serres, & Vivalda, 2013;Bakir, Othman, Fevotte, & Hammouri, 2006;Bristeau, Dorveaux, Vissière, & Petit, 2010;Dymkov, Gaishun, Rogers, Galkowski, & Owens, 2004;Jazwinski, 1970;Karafyllis & Kravaris, 2009;Nadri & Hammouri, 2003;Nicolao & Strada, 1998;Sebesta & Boizot, 2014;Sebesta, Boizot, Busvelle, & Sachau, 2010;Song & Shin, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Aguilar-López and Maya-Yescas (2005) developed a sliding mode observer for a polymerisation process. Bakir et al (2006) suggested a high gain observer for a batch crystalliser, which is applicable, when the nuclei are measurable, because then the model equations are given directly in observability normal form. For this work, two modern state estimation techniques have been chosen, which to our knowledge have not yet been applied to population balance models before.…”
Section: Introductionmentioning
confidence: 99%